Suffering and Flourishing - Stump, Eleonore (2023)
While recognizing that there is something right about the contemporary rejection of suffering as bad, this contribution develops the intuition that there is nonetheless something worth exploring in the Christian attitude towards suffering as a gift. It looks closely at the relevant Christian doctrines to see what can be said to explain this attitude towards suffering and to distinguish it from the neighboring perverse attitude that sees suffering as an intrinsic good. Taking its point of departure in Paul’s thought about suffering, glory and consolation in 2 Corinthians, the article approaches the nature and effects of suffering by distinguishing different modes of human flourishing and thriving. The argument is illustrated by the examples of Harriet Tubman and Harriet McBryde Johnson.